POLA AKAD PERSONAL SHOPPER DALAM JUAL BELI ONLINE DI KOTA BANJARMASIN KALIMANTAN SELATAN - Sa'adah Sa'adah; Hanafiah Hanafiah; Emelia Rizki Maulida (JOURNAL OF ISLAMIC AND LAW STUDIES, 2019)
Abstract"Personal Shopper" is a buy-in service or better known as an online deposit service, a system offered by individuals to "buy" something which is then added to the cost of compensation or service, which is usually called a jastip fee. explained Personal Shopper which is a job in and out of shops, malls or large marchants with several well-known brands in accordance with the wishes of customers who believe in their services. The items sought are not only at the local level, it is not uncommon for requests for goods from abroad. This research is based on the background of many contract variations used by the shopper personal so that the contract that is supposed to be seen according to the muqalah fiqh perspective must therefore be known how the entrusted services and perceptions of practitioners on online entrusted services. The formulation of the problem in this study is How Online Shop Practitioners' Perception of Service Contracts Received Online is then analyzed according to the Muamalah Fiqh Perspective as for the purpose of the study is to find out the perceptions of online shop practitioners on the contract of online deposit services. The analysis technique is qualitative descriptive, to collect data needed by the author using observing techniques followed by interview techniques with shopper personal and online shop practitioners. After the collected data is processed with editing and categorization techniques. To obtain conclusions, an analysis of the data obtained is carried out. In the analysis there are 3 different case variations, so that there are 3 different laws of each shopper personal variation, variation 1 (cases III, IV and V) of this practice is not justified in Islam because of the element of combining two contracts in one transaction, in variation 2 ( case II) this practice is permissible because it is in accordance with the greeting and ijarah agreement, and in variation 3 (case I) the practice of personal shopper is invalid because of the element of dishonesty and gharar. Abstrak“Personal Shopper” adalah Jasa titip beli atau yang lebih dikenal jasa titip online merupakan sistem yang ditawarkan oleh perorangan untuk “membelikan” sesuatu yang kemudian ditambahkan biaya imbalan atau uang jasanya yang biasa disebut ongkos jastip. jelasnya Personal Shopper yaitu sebuah pekerjaan keluar masuk toko, mall atau marchant besar dengan beberapa merek terkenal sesuai dengan keinginan para pelanggan yang percaya pada jasa mereka. Barang yang dicari tidak hanya ditingkat lokal, tidak jarang adanya permintaan untuk barang-barang dari luar negeri. Penelitian ini dilatar belakangi menggenai banyak nya variasi akad yang digunakan oleh personal shopper shingga teraibaikan akad yang seharusnya dilihat menurut perspektif fiqih muamalah oleh karena itu harusnya diketahui bagaimana jasa titip dan persepsi praktisi pada jasa titip online. Rumusan masalah dalam penelitian ini adalah Bagaimana Persepsi Praktisi Online Shop Terhadap Akad Jasa Titip Online kemudian dianalisis menurut Perspektif Fiqih Muamalah adapun tujuan penelitian adalah untuk mengetahui persepsi praktisi online shop terhadap akad jasa titip online. Teknik analisis adalah deskripti kualitatif, untuk mengumpulkan data yang diperlukan penulis menggunakan teknik mengamati di lanjutkan dengan teknik wawancara dengan para personal shopper dan praktisi online shop. Setelah data terkumpul diolah dengan teknik editing dan kategorisasi. Untuk memperoleh kesimpulan, dilakukan analisis terhadap data yang didapat. Pada analisis terdapat 3 variasi kasus yang berbeda, sehingga terdapat 3 hukum yang berbeda dari setiap variasi personal shopper, variasi 1 (kasus III,IV dan V) praktik ini tidak dibenarkan dalam islam karena unsur penggabungan dua akad dalam satu transaksi, pada variasi 2 (kasus II) praktik ini dibolehkan karena sesuai dengan akad salam maupun ijarah, dan pada variasi 3 (kasus I) praktik yang dilakukan personal shopper tidak sah karena adanya unsur ketidak jujuran dan gharar.Kata kunci : Persepsi, Praktisi, Akad.